Advances in Science, Engineering and Technology in the Kyrgyz Republic - Opportunities for Malaysia - Seminar on advances in science, engineering and technology in the Kyrgyz Republic - opportunities for Malaysia (1998 : Malaysia) (Kuala Lumpur : Akademi Sains Malaysia, 1998)
39